Commutative subalgebras of three first-order symmetry operators and separation of variables in the wave equation; Soviet Physics Journal; Vol. 33, iss. 5 - Bagrov V. G. Vladislav Gavriilovich; Samsonov B. F.; Shapovalov A. V. Aleksandr Vasilyevich; Shirokov I. V. (1990, 1990)
Title screen